A 3D Trilayered CNT/MoSe2/C Heterostructure with an Expanded MoSe2 Interlayer Spacing for an Efficient Sodium Storage. Issue 30 (2nd July 2019) - Yousaf, Muhammad; Wang, Yunsong; Chen, Yijun; Wang, Zhipeng; Firdous, Attia; Ali, Zeeshan; Mahmood, Nasir; Zou, Ruqiang; Guo, Shaojun; Han, Ray P. S.
Abstract: Freestanding composite structures with embedded transition metal dichalcogenides (TMDCs) as the active material are highly attractive in the development of advanced electrodes for energy storage devices. Most 3D electrodes consist of a bilayer design involving a core–shell combination. To further enhance the gravimetric and areal capacities, a 3D trilayer design is proposed that has MoSe2 as the TMDC sandwiched in‐between an inner carbon nanotube (CNT) core and an outer carbon layer to form a CNT/MoSe2 /C framework. The CNT core creates interconnected pathways for the e − /Na + conduction, while the conductive inert carbon layer not only protects the corrosive environment between the electrolyte and MoSe2 but also is fully tunable for an optimized Na + storage. This unique heterostructure is synthesized via a solvothermal‐carbonization approach. Due to annealing under a confined structural configuration, MoSe2 interlayer spaces are expanded to facilitate a faster Na + diffusion. It is shown that an ≈3 nm thick carbon layer yielded an optimized anode for a sodium‐ion battery. The 3D porosity of the heterostructure remains intact after an intense densification process to produce a high areal capacity of 4.0 mAh cm −2 and a high mass loading of 13.9 mg cm −2 with a gravimetric capacity of 347 mAh g −1 at 500 mA g −1 after 500 cycles. Abstract : A 3D trilayer heterostructure (3D CNT/MoSe2 /C) (CNT: carbon nanotube) is fabricated in which expanded MoSe2 is sandwiched in‐between the carbon nanotube and the carbon layer with a tunable thickness of outer carbon layer. The 3D CNT/MoSe2 /C heterostructures are highly porous and can be densified by compaction. Representative CNT/MoSe2 /C present adequately high mass loading, high areal capacity, and excellent cyclic stability for sodium‐ion batteries.